A hydrolysis-resistant bopa film for power pouch cells and a method for preparing the same
Patent Information
- Application Number
- CN202311010610.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-08-11
AI Technical Summary
[0005]本发明的目的在于克服现有技术存在的缺陷,提供一种动力软包电池用的抗水解的BOPA薄膜,解决BOPA薄膜不抗热水浸泡,容易发生降解,进而导致水分侵入,漏液等,从而破坏电池结构的问题
[0023]1、本发明制得的动力软包电池用的抗水解的BOPA薄膜,不仅具有抗高低温水解性能,同时还具有优异的冲深性能、耐热性能、耐高温氧化和腐蚀、耐磨性能及优异的力学性能等,在动力电池领域方面具有很好的应用前景。
Smart Images

Figure CN117106299B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thin film technology for power batteries, specifically relating to a hydrolysis-resistant BOPA film for power soft-pack batteries and its preparation method. Background Technology
[0002] Lithium-ion batteries are widely used in electric vehicles and other fields due to their excellent power output and long lifespan. However, the performance of lithium-ion batteries is quite sensitive to temperature changes. If the battery pack of an electric vehicle cannot dissipate heat in time at high temperatures, it will lead to excessively high battery system temperature or uneven temperature distribution, reducing the battery's charge and discharge cycle efficiency. In severe cases, it can even lead to thermal runaway, affecting the battery's safety and reliability.
[0003] Liquid cooling offers high efficiency and rapid cooling, meeting the needs of high-power charging and discharging. With the increasing application of pouch batteries in electric vehicles, the demand for liquid-cooled thermal management systems for pouch power battery packs is gradually emerging. Because BOPA film molecules contain polar amide groups (-CO-NH-), the -NH- groups can form hydrogen bonds with -C=O groups. The formation of hydrogen bonds is one of the important reasons for the high crystallinity of polyamides. However, in production, not all polyamide molecules can crystallize and coordinate; some non-crystalline polyamide polar groups remain. The amide groups in these non-crystalline polyamide molecular chains can coordinate with water, giving the polyamide film high water absorption. Under certain temperatures, it is not resistant to hot water immersion and is prone to degradation. After being assembled into a power pouch battery, prolonged immersion in aqueous liquids at certain temperatures can cause a series of problems such as interlayer separation, water intrusion, and leakage, thereby damaging the battery structure and affecting product performance.
[0004] Therefore, it is essential to develop a hydrolysis-resistant BOPA film for power soft-pack batteries to solve the aforementioned problems. Summary of the Invention
[0005] The purpose of this invention is to overcome the defects of the existing technology and provide a hydrolysis-resistant BOPA film for power soft-pack batteries, solving the problem that BOPA film is not resistant to hot water immersion, is prone to degradation, and thus leads to water intrusion, leakage, etc., thereby damaging the battery structure.
[0006] To achieve the above objectives, one of the technical solutions of the present invention is: a hydrolysis-resistant BOPA film for power soft-pack batteries, comprising an inner layer, a core layer and a surface layer from the inside out, wherein the inner layer, core layer and surface layer are co-extruded in three layers by a casting machine and then obtained by longitudinal and transverse biaxial stretching.
[0007] Furthermore, the inner layer comprises, by weight percentage, 96.5-98.0 wt% nylon chips, 1.0-1.5 wt% anti-hydrolysis agent, 0.5-1.0 wt% opening agent and 0.5-1.0 wt% slip agent.
[0008] Furthermore, the core layer comprises, by weight percentage, 98.0-98.5 wt% nylon chips and 1.5-2.0 wt% hydrolysis-resistant additives.
[0009] Furthermore, the surface layer comprises, by weight percentage, 92.5-95.5 wt% nylon chips, 2.5-3.5 wt% anti-hydrolysis agent, 1.0-2.0 wt% magnesium oxide, 0.5-1.0 wt% opening agent and 0.5-1.0 wt% slip agent.
[0010] Furthermore, the nylon chips are made from at least one or more of nylon 6, a copolymer of nylon 6 and nylon 6,6, and nylon 612.
[0011] Furthermore, the anti-hydrolysis aid is a polycarbodiimide compound with a carbodiimide equivalent of 17%-23% and a molecular weight of 30,000-40,000.
[0012] Furthermore, the slip agent is one or more of erucamide, oleamide, silicone oil, silicone, and polyethylene wax.
[0013] Furthermore, the magnesium oxide has a particle size of 30-50 nm and a specific surface area of 30-50 m². 2 / g.
[0014] Furthermore, the opening agent is one or more of the following: silica, talc, zeolite, diatomaceous earth, calcium carbonate, and clay.
[0015] Furthermore, the thickness of the BOPA film is 15-25 μm.
[0016] Furthermore, the thickness of the inner layer is 1.5-2.5 μm, the thickness of the outer layer is 1.5-2.5 μm, and the thickness of the core layer is 10-22 μm.
[0017] To achieve the above objectives, the second technical solution of the present invention is: a method for preparing a hydrolysis-resistant BOPA film for power soft-pack batteries, specifically including the following steps:
[0018] (1) Nylon chips, anti-hydrolysis additives, opening agents and slip agents are mixed according to the composition ratio of the inner layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain inner layer masterbatch for later use;
[0019] (2) Nylon chips and anti-hydrolysis additives are mixed according to the composition ratio of the core layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain core layer masterbatch for later use;
[0020] (3) Nylon chips, anti-hydrolysis additives, magnesium oxide, opening agent and slip agent are mixed according to the composition ratio of the surface layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain surface masterbatch for later use;
[0021] (4) The masterbatch of each film layer prepared above is melted and extruded by different extruders in the temperature range of 180℃~280℃ and then merged into the same T-die. The melt left in the die is cooled by the cooling roller to form a cast sheet. Then it is stretched in both longitudinal and transverse directions and shaped. Then the inner layer is corona treated to make the corona value reach 45-60dyn / cm, so as to obtain a hydrolysis resistant BOPA film for power soft pack battery.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0023] 1. The hydrolysis-resistant BOPA film for power soft-pack batteries prepared by this invention not only has resistance to high and low temperature hydrolysis, but also has excellent deep-drawing performance, heat resistance, high-temperature oxidation and corrosion resistance, wear resistance and excellent mechanical properties, and has a good application prospect in the field of power batteries.
[0024] 2. The anti-hydrolysis additive added in this invention is a polycarbodiimide compound that can react with free acids and water, and can also crosslink with degraded polymer fragments, extending the polymer chain structure, protecting the polymer skeleton structure, and thus improving the hydrolysis resistance.
[0025] 3. The present invention adds magnesium oxide additive, which has good high temperature stability and can maintain its physical and chemical properties in high temperature environment for a long time. It is not easy to react with other elements or compounds, thus improving the temperature resistance of the film. At the same time, magnesium oxide can also improve the film's resistance to high temperature oxidation and corrosion. Attached Figure Description
[0026] Figure 1 This refers to a hydrolysis-resistant BOPA film for a power soft-pack battery as described in Example 1.
[0027] Among them, 10 is the inner layer, 20 is the core layer, and 30 is the outer layer. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in more detail below with reference to the accompanying drawings and specific embodiments. However, the scope of protection of this invention is not limited to these embodiments. The same reference numerals throughout the text always represent the same elements, and similar reference numerals represent similar elements.
[0029] In the description of this invention, it should be understood that the terms "upper," "lower," "front," "rear," "left," "right," "horizontal," "vertical," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the perspective views in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0030] A hydrolysis-resistant BOPA film for power soft-pack batteries comprises, from the inside out, an inner layer, a core layer, and a surface layer. The inner layer, core layer, and surface layer are co-extruded in three layers by a casting machine and then biaxially stretched.
[0031] The inner layer comprises, by weight percentage, 96.5-98.0 wt% nylon chips, 1.0-1.5 wt% anti-hydrolysis additive, 0.5-1.0 wt% opening agent and 0.5-1.0 wt% slip agent.
[0032] The core layer comprises, by weight percentage, 98.0-98.5 wt% nylon chips and 1.5-2.0 wt% hydrolysis resistant additives.
[0033] The surface layer comprises, by weight percentage, 92.5-95.5 wt% nylon chips, 2.5-3.5 wt% anti-hydrolysis additive, 1.0-2.0 wt% magnesium oxide, 0.5-1.0 wt% opening agent and 0.5-1.0 wt% slip agent.
[0034] The nylon chips are made from at least one or more of nylon 6, a copolymer of nylon 6 and nylon 6,6, and nylon 612.
[0035] The anti-hydrolysis agent is a polycarbodiimide compound with a carbodiimide equivalent of 17%-23% and a molecular weight of 30,000-40,000.
[0036] The slip agent is one or more of erucamide, oleamide, silicone oil, silicone, and polyethylene wax.
[0037] The magnesium oxide has a particle size of 30-50 nm and a specific surface area of 30-50 m². 2 / g.
[0038] The opening agent is one or more of the following: silicon dioxide, talc, zeolite, diatomaceous earth, calcium carbonate, and clay.
[0039] The thickness of the BOPA film is 15-25 μm.
[0040] The inner layer has a thickness of 1.5-2.5 μm, the outer layer has a thickness of 1.5-2.5 μm, and the core layer has a thickness of 10-22 μm.
[0041] A method for preparing a hydrolysis-resistant BOPA film for power soft-pack batteries specifically includes the following steps:
[0042] (1) Nylon chips, anti-hydrolysis additives, opening agents and slip agents are mixed according to the composition ratio of the inner layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain inner layer masterbatch for later use;
[0043] (2) Nylon chips and anti-hydrolysis additives are mixed according to the composition ratio of the core layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain core layer masterbatch for later use;
[0044] (3) Nylon chips, anti-hydrolysis additives, magnesium oxide, opening agent and slip agent are mixed according to the composition ratio of the surface layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain surface masterbatch for later use;
[0045] (4) The masterbatch of each film layer prepared above is melted and extruded by different extruders in the temperature range of 180℃~280℃ and then merged into the same T-die. The melt left in the die is cooled by the cooling roller to form a cast sheet. Then it is stretched in both longitudinal and transverse directions and shaped. Then the inner layer is corona treated to make the corona value reach 45-60dyn / cm, so as to obtain a hydrolysis resistant BOPA film for power soft pack battery.
[0046] Example 1
[0047] A hydrolysis-resistant BOPA film for use in power soft-pack batteries, such as Figure 1 As shown, the film comprises, from the inside out, an inner layer 10, a core layer 20, and a surface layer 30. These three layers are co-extruded using a casting machine and then biaxially stretched. The BOPA film has a thickness of 25 μm, with the inner layer being 2.5 μm thick, the surface layer 2.5 μm thick, and the core layer 20 μm thick. The inner layer of the BOPA film consists of 96.5 wt% nylon chips, 1.5 wt% anti-hydrolysis agent, 1.0 wt% opening agent, and 1.0 wt% slip agent; the core layer consists of 98.0 wt% nylon chips and 2.0 wt% anti-hydrolysis agent; and the surface layer consists of 92.5 wt% nylon chips, 3.5 wt% anti-hydrolysis agent, 2.0 wt% magnesium oxide, 1.0 wt% opening agent, and 1.0 wt% slip agent.
[0048] The anti-hydrolysis additive used in this embodiment consists of a polycarbodiimide compound with a carbodiimide equivalent of 17% and a molecular weight of 30,000. The magnesium oxide used for the surface layer has a particle size of 30 nm and a specific surface area of 30 m². 2 / g. Nylon chips are made from Nylon 6. The slip agent consists of erucamide and oleamide in a mass ratio of 7:3. The opening agent consists of silica and talc in a mass ratio of 1:1.
[0049] The hydrolysis-resistant BOPA film used in the above-mentioned power soft-pack battery is prepared by the following method, specifically including the following steps:
[0050] Step a: Mix nylon chips, anti-hydrolysis additives, opening agents and slip agents according to the composition ratio of the inner layer, and then melt-blend, extrude and granulate the mixture using a twin-screw extruder to obtain the inner layer masterbatch for later use;
[0051] Step b: Mix nylon chips with anti-hydrolysis additives according to the composition ratio of the core layer, and then melt-blend, extrude, and granulate the mixture using a twin-screw extruder to obtain core layer masterbatch for later use.
[0052] Step c: Mix nylon chips, anti-hydrolysis additive, magnesium oxide, opening agent and slip agent according to the composition ratio of the surface layer, and then melt-blend, extrude and granulate the mixture through a twin-screw extruder to obtain the surface masterbatch for later use.
[0053] Step d: The masterbatches of each film layer prepared above are melted and extruded by different extruders at a temperature range of 180℃~280℃ and then converged into the same T-die. The melt left in the die is cooled by the cooling roller to form a cast sheet. Then, it is stretched in both longitudinal and transverse directions and shaped. Then, the inner layer is corona treated to make the corona value reach 52dyn / cm, so as to obtain a hydrolysis resistant BOPA film for power soft pack batteries.
[0054] Example 2
[0055] A hydrolysis-resistant BOPA film for power soft-pack batteries is prepared using the method described in Example 1, with the difference that: the hydrolysis-resistant additive is composed of a polycarbodiimide compound with a carbodiimide equivalent of 23% and a molecular weight of 40,000; the magnesium oxide has a particle size of 50 nm and a specific surface area of 50 m². 2 / g; the inner layer consists of 98.0wt% nylon chips, 1.0wt% anti-hydrolysis additive, 0.5wt% opening agent and 0.5wt% slip agent; the core layer consists of 98.5wt% nylon chips and 1.5wt% anti-hydrolysis additive; the outer layer consists of 95.5wt% nylon chips, 2.5wt% anti-hydrolysis additive, 1.0wt% magnesium oxide, 0.5wt% opening agent and 0.5wt% slip agent.
[0056] Example 3
[0057] A hydrolysis-resistant BOPA film for power soft-pack batteries is prepared using the method described in Example 1, with the difference that: the hydrolysis-resistant additive is composed of a polycarbodiimide compound with a carbodiimide equivalent of 20% and a molecular weight of 35,000; and the magnesium oxide has a particle size of 40 nm and a specific surface area of 40 m². 2 / g; the inner layer consists of 97.25wt% nylon chips, 1.25wt% anti-hydrolysis additive, 0.75wt% opening agent and 0.75wt% slip agent; the core layer consists of 98.25wt% nylon chips and 1.75wt% anti-hydrolysis additive; the outer layer consists of 94.0wt% nylon chips, 3.0wt% anti-hydrolysis additive, 1.5wt% magnesium oxide, 0.75wt% opening agent and 0.75wt% slip agent.
[0058] Example 4
[0059] A hydrolysis-resistant BOPA film for power soft-pack batteries is prepared using the method described in Example 1, with the difference being that the thickness of the BOPA film is 15 μm, wherein the thickness of the inner layer is 2.0 μm, the thickness of the outer layer is 2.0 μm, and the thickness of the core layer is 11 μm.
[0060] Example 5
[0061] A hydrolysis-resistant BOPA film for power soft-pack batteries is prepared using the method described in Example 1, with the difference that: the hydrolysis-resistant additive is composed of a polycarbodiimide compound with a carbodiimide equivalent of 17% and a molecular weight of 30,000; the magnesium oxide has a particle size of 30 nm and a specific surface area of 30 m². 2 / g; the inner layer consists of 96.5wt% nylon chips, 1.5wt% anti-hydrolysis agent, 1.0wt% opening agent and 1.0wt% slip agent; the core layer consists of 98.0wt% nylon chips and 2.0wt% anti-hydrolysis agent; the outer layer consists of 92.5wt% nylon chips, 3.5wt% anti-hydrolysis agent, 2.0wt% magnesium oxide, 1.0wt% opening agent and 1.0wt% slip agent; the nylon chips are made of a copolymer of nylon 6 and nylon 6,6; the slip agent is composed of erucamide and silicone oil in a mass ratio of 7:3; the opening agent is composed of zeolite and diatomaceous earth in a mass ratio of 3:7; the thickness of the BOPA film is 25μm, of which the thickness of the inner layer is 2.5μm, the thickness of the outer layer is 2.5μm, and the thickness of the core layer is 20μm.
[0062] Comparative Example 1
[0063] A BOPA film, from the inside out, comprises an inner layer, a core layer, and an outer layer. The composition of each layer differs from that in Example 1 in that: the inner layer consists of 98.0 wt% nylon chips, 1.0 wt% opening agent, and 1.0 wt% slip agent; the core layer consists of 100 wt% nylon chips; and the outer layer consists of 98.0 wt% nylon chips, 1.0 wt% opening agent, and 1.0 wt% slip agent.
[0064] A BOPA film was prepared by the following method:
[0065] Step a: Mix nylon chips, opening agent and slip agent according to the composition ratio of the inner layer, and then melt-blend, extrude and granulate the mixture through a twin-screw extruder to obtain the inner layer masterbatch for later use;
[0066] Step b: Prepare nylon slices according to the core layer material;
[0067] Step c: Mix nylon chips, opening agent and slip agent according to the mass ratio of the surface layer, and then melt-blend, extrude and granulate the mixture through a twin-screw extruder to obtain the surface layer masterbatch for later use;
[0068] Step d: The masterbatches and nylon chips obtained above are melted and extruded by different extruders at a temperature range of 180℃-280℃ and then converged into the same T-die. The melt left in the die is cooled by the cooling roller to form a cast sheet. Then, it is stretched in both longitudinal and transverse directions and shaped. Then, the inner layer is corona treated to make the corona value reach 52dyn / cm, so as to obtain a hydrolysis resistant BOPA film for power soft pack batteries.
[0069] Comparative Example 2
[0070] A BOPA film, the composition of which differs from that of Example 1, is as follows: the anti-hydrolysis agent is composed of a polycarbodiimide compound with a carbodiimide equivalent of 17% and a molecular weight of 30,000; the inner layer is composed of 96.5 wt% nylon chips, 1.5 wt% anti-hydrolysis agent, 1.0 wt% opening agent, and 1.0 wt% slip agent; the core layer is composed of 98.0 wt% nylon chips and 2.0 wt% anti-hydrolysis agent; and the outer layer is composed of 94.5 wt% nylon chips, 3.5 wt% anti-hydrolysis agent, 1.0 wt% opening agent, and 1.0 wt% slip agent.
[0071] A BOPA film was prepared by the following method:
[0072] Step a: Mix nylon chips, anti-hydrolysis additive, opening agent and slip agent according to the inner layer ratio, and then melt-blend, extrude and granulate the mixture using a twin-screw extruder to obtain inner layer masterbatch for later use;
[0073] Step b: Mix nylon chips with anti-hydrolysis additives according to the core layer ratio, and then melt-blend, extrude, and granulate the mixture using a twin-screw extruder to obtain core layer masterbatch for later use;
[0074] Step c: Mix nylon chips, anti-hydrolysis additive, opening agent and slip agent according to the above surface layer ratio, and then melt-blend, extrude and granulate the mixture through a twin-screw extruder to obtain surface layer masterbatch for later use;
[0075] Step d: The raw material mixtures of each film layer are melted and extruded by different extruders at a temperature range of 180℃~280℃ and then converged into the same T-die. The melt left in the die is cooled by the cooling roller to form a cast sheet, which is then stretched in both longitudinal and transverse directions and shaped. Then, the inner layer is corona treated to make the corona value reach 52dyn / cm, thus obtaining a hydrolysis-resistant BOPA film for power soft pack batteries.
[0076] Comparative Example 3
[0077] A BOPA film, the composition of which differs from that of Example 1, is as follows: the inner layer consists of 98.0 wt% nylon chips, 1.0 wt% opening agent, and 1.0 wt% slip agent; the core layer consists of 100.0 wt% nylon chips; and the outer layer consists of 96.0 wt% nylon chips, 2.0 wt% magnesium oxide, 1.0 wt% opening agent, and 1.0 wt% slip agent; the magnesium oxide has a particle size of 30 nm and a specific surface area of 30 m². 2 / g.
[0078] A BOPA film was prepared by the following method:
[0079] Step a: Mix nylon chips, opening agent and slip agent according to the inner layer ratio, melt blend, extrude and granulate through a twin-screw extruder to obtain inner layer masterbatch for later use;
[0080] Step b: Prepare nylon slices according to the materials required for the core layer;
[0081] Step c: Mix nylon chips, magnesium oxide, opening agent and slip agent according to the above surface layer ratio, and then melt-blend, extrude and granulate the mixture using a twin-screw extruder to obtain surface layer masterbatch for later use;
[0082] Step d: The raw material mixtures of each film layer are melted and extruded by different extruders at a temperature range of 180℃-280℃ and then converged into the same T-die. The melt left in the die is cooled by the cooling roller to form a cast sheet, which is then stretched in both longitudinal and transverse directions and shaped. The inner layer is then corona treated to achieve a corona value of 52dyn / cm, resulting in a hydrolysis-resistant BOPA film for power soft-pack batteries.
[0083] Comparative Example 4
[0084] A BOPA film is prepared in the same way as in Example 1, except that the anti-hydrolysis agent is composed of a polycarbodiimide compound with a molecular weight of 10,000 and a carbodiimide equivalent of 10%.
[0085] Comparative Example 5
[0086] A BOPA film is prepared in the same way as in Example 1, except that the anti-hydrolysis agent is composed of a polycarbodiimide compound with a carbodiimide equivalent of 27% and a molecular weight of 50,000.
[0087] Comparative Example 6
[0088] A BOPA film is prepared in the same way as in Example 1, except that: the inner layer consists of 97.5 wt% nylon chips, 0.5 wt% anti-hydrolysis agent, 1.0 wt% opening agent, and 1.0 wt% slip agent; the core layer consists of 99.0 wt% nylon chips and 1.0 wt% anti-hydrolysis agent; and the outer layer consists of 95.0 wt% nylon chips, 1.0 wt% anti-hydrolysis agent, 2.0 wt% magnesium oxide, 1.0 wt% opening agent, and 1.0 wt% slip agent.
[0089] Comparative Example 7
[0090] A BOPA film is prepared in the same way as in Example 1, except that: the inner layer consists of 93.0 wt% nylon chips, 5.0 wt% anti-hydrolysis agent, 1.0 wt% opening agent and 1.0 wt% slip agent; the core layer consists of 96.0 wt% nylon chips and 4.0 wt% anti-hydrolysis agent; and the outer layer consists of 90.0 wt% nylon chips, 6.0 wt% anti-hydrolysis agent, 2.0 wt% magnesium oxide, 1.0 wt% opening agent and 1.0 wt% slip agent.
[0091] Comparative Example 8
[0092] A BOPA film is prepared in the same way as in Example 1, except that: the inner layer consists of 96.5 wt% nylon chips, 1.5 wt% anti-hydrolysis agent, 1.0 wt% opening agent, and 1.0 wt% slip agent; the core layer consists of 98.0 wt% nylon chips and 2.0 wt% anti-hydrolysis agent; and the outer layer consists of 94.0 wt% nylon chips, 3.5 wt% anti-hydrolysis agent, 0.5 wt% magnesium oxide, 1.0 wt% opening agent, and 1.0 wt% slip agent.
[0093] Comparative Example 9
[0094] A BOPA film is prepared in the same way as in Example 1, except that: the inner layer consists of 96.5 wt% nylon chips, 1.5 wt% anti-hydrolysis agent, 1.0 wt% opening agent, and 1.0 wt% slip agent; the core layer consists of 98.0 wt% nylon chips and 2.0 wt% anti-hydrolysis agent; and the outer layer consists of 90.5 wt% nylon chips, 3.5 wt% anti-hydrolysis agent, 4.0 wt% magnesium oxide, 1.0 wt% opening agent, and 1.0 wt% slip agent.
[0095] The BOPA films prepared in Examples 1-5 and Comparative Examples 1-9 were subjected to performance testing according to the following method:
[0096] 1. Haze test: Tested according to GB 2410-1980 Test Method for Light Transmittance and Haze of Transparent Plastics;
[0097] 2. Tensile strength and elongation at break: Tested according to GB / T 13022-1991, "Test Method for Tensile Properties of Plastic Films". The specimen is a long strip 150 mm long and (15 ± 0.1) mm wide, with a clamping distance of 100 mm and a test speed of (250 ± 25) mm / min.
[0098] 3. Moist heat aging test: Cut the sample into a long strip with a length of 150 mm and a width of (15±0.1) mm, place it in a constant temperature and humidity chamber with a temperature of 85℃ and a humidity of 85%, and after one week, take it out and test the tensile strength and elongation at break according to the provisions of GBT 13022-1991 Test Method for Tensile Properties of Plastic Films.
[0099] 4. Heat shrinkage rate: Tested according to GB / T 12027-2004 Test method for dimensional change rate of plastic film and sheet under heating, with test conditions of (160±2)℃ and time of 5min.
[0100] The performance test results of the BOPA films prepared in Examples 1-5 and Comparative Examples 1-9 are shown in the table below:
[0101] Table 1. Performance test results of different BOPA films
[0102]
[0103] As can be seen from the above film performance tests, the BOPA films prepared in Examples 1-5 have better hydrolysis resistance and lower heat shrinkage compared with Comparative Examples 1-9; at the same time, there is no significant difference in haze, initial tensile strength and initial elongation at break.
[0104] Comparative Example 1, being a simple BOPA film without any additives, showed a significant decrease in tensile strength and elongation at break after the damp heat aging test, and also exhibited relatively high heat shrinkage. Comparative Example 2, with only an anti-hydrolysis additive, showed a decrease in tensile strength and elongation at break after the damp heat aging test, and also relatively high heat shrinkage. Comparative Example 3, with only magnesium oxide added, showed a significant decrease in tensile strength and elongation at break after the damp heat aging test, and also slightly higher heat shrinkage. Comparative Example 4, due to the low equivalent and low molecular weight of carbodiimide in the anti-hydrolysis agent, showed a significant decrease in peel strength and elongation at break after the damp heat aging test. Comparative Example 5, due to the high equivalent and low molecular weight of carbodiimide in the added anti-hydrolysis agent, showed a significant decrease in peel strength and elongation at break. The amount of magnesium oxide added is relatively large, which not only affects the tensile strength and elongation at break of the film itself, but also makes the film more brittle after the damp heat aging test, resulting in a significant decrease in tensile strength and elongation at break. In Comparative Example 6, due to the insufficient addition of anti-hydrolysis additives, the tensile strength and elongation at break both decreased after the damp heat aging test. In Comparative Example 7, due to the excessive addition of anti-hydrolysis additives, the film became brittle after the damp heat aging test, and both tensile strength and elongation at break decreased. In Comparative Example 8, the insufficient addition of magnesium oxide resulted in low temperature resistance of the film, which not only affected the tensile strength and elongation at break after the damp heat aging test, but also affected the thermal shrinkage. In Comparative Example 9, the excessive addition of magnesium oxide affected the transparency of the film itself, resulting in excessive haze.
[0105] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A hydrolysis-resistant BOPA film for use in power soft-pack batteries, characterized in that, The composition, from the inside out, comprises an inner layer, a core layer, and a surface layer. The inner layer, by weight percentage, comprises 96.5-98.0 wt% nylon chips, 1.0-1.5 wt% anti-hydrolysis additive, 0.5-1.0 wt% opening agent, and 0.5-1.0 wt% slip agent. The core layer, by weight percentage, comprises 98.0-98.5 wt% nylon chips and 1.5-2.0 wt% anti-hydrolysis additive. The surface layer, by weight percentage, comprises 92.5-95.5 wt% nylon chips, 2.5-3.5 wt% anti-hydrolysis additive, 1.0-2.0 wt% magnesium oxide, 0.5-1.0 wt% opening agent, and 0.5-1.0 wt% slip agent. wt% slip agent; the anti-hydrolysis additive is a polycarbodiimide compound with a carbodiimide equivalent of 17%-23% and a molecular weight of 30,000-40,000; the magnesium oxide has a particle size of 30-50 nm and a specific surface area of 30-50 m². 2 / g; the thickness of the BOPA film is 15-25μm; the thickness of the inner layer is 1.5-2.5μm, the thickness of the outer layer is 1.5-2.5μm, and the thickness of the core layer is 10-22μm.
2. The BOPA film as described in claim 1, characterized in that, The nylon chips are made from at least one or more of nylon 6, a copolymer of nylon 6 and nylon 6,6, and nylon 612.
3. The BOPA film as described in claim 1, characterized in that, The slip agent is one or more of erucamide, oleamide, silicone oil, and polyethylene wax.
4. The BOPA film as described in claim 1, characterized in that, The opening agent is one or more of the following: silica, talc, zeolite, diatomaceous earth, calcium carbonate, and clay.
5. A method for preparing a BOPA thin film as described in any one of claims 1-4, characterized in that, Includes the following steps: (1) Nylon chips, anti-hydrolysis additives, opening agents and slip agents are mixed according to the composition ratio of the inner layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain inner layer masterbatch for later use; (2) Nylon chips and anti-hydrolysis additives are mixed according to the composition ratio of the core layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain core layer masterbatch for later use; (3) Nylon chips, anti-hydrolysis additive, magnesium oxide, opening agent and slip agent are mixed according to the composition ratio of the surface layer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain surface masterbatch for later use; (4) The masterbatch of each film layer prepared above is melted and extruded by different extruders and then merged into the same T-die. The melt left in the die is cooled by the cooling roller to form a cast sheet. Then it is stretched in both longitudinal and transverse directions and shaped. Then the inner layer is corona treated so that the corona value reaches 45-60 dyn / cm to obtain a hydrolysis resistant BOPA film for power soft pack batteries.
6. The preparation method according to claim 5, characterized in that, The extrusion temperature in step (4) is 180-280℃.
Citation Information
Patent Citations
Waterproof alcoholysis high-temperature resistant renewable nylon 66 composite material and preparation method thereof
CN103450678A
Glass fiber reinforced nylon 66 composite material for panel of dish-washing machine and preparation method thereof
CN105111730A